MELESTARIAN KAWASAN KONSERVASI SEBAGAI LANDASAN BUDAYA DALAM PERENCANAAN KOTA PEKALONGAN - Eko Punto Hendro; Suzanna Ratih Sari (Diponegoro University, 2018)
Pekalongan formed through a long and unique history, which is characterized by a variety of historical relics and ancient buildings the main building. Starting from this, it seems we need a comprehensive conceptual thinking to handle the pearls in Pekalongan city, which still looks dull and does not appear to shine. Pekalongan city government itself also can not see that the potential of the region and the ancient building is of pearls are still dull and hidden, which can be polished so shiny and attract attention. They prefer talkative build buildings and malls without careful planning, and often displacing precisely these historic buildings. From sentences above, presumably, this research is needed to handle the pearls through the development of the concept of conservation, namely the concept of the arrangement, preservation, and development of the areas historic city of Pekalongan, and certainly is one of the bases for planning and development of culture and tourism city. Regulation on the protection of historic buildings the city is already there, but it is still necessary regulatory or conservation regulation in order to historic district Pekalongan sustainable, not just the building alone.